Methylation of chloroplast DNAs in the life cycle of Chlamydomonas - Royer, Hans-Dieter (1979)
Methylation patterns of Chlamydomonas chloroplast DNAs (chlDNAs) were examined in the vegetative, gametic, and zygotic stages of the life cycle. Restriction endo-nuclease fragment patterns produced by EcoRI, BamHI, Hpa II, and Msp I were compared; the last two cleave DNA at the sequence C-C-G-G, but Hpa II is blocked by prior methylation of the internal cytidine whereas Msp I is not. chlDNAs from vegetative cells of both mating types showed no evidence of methylation at C-C-G-G. Gametic mt+ chlDNA was heavily methylated at C-C-G-G, whereas the homologous chlDNA from mt- gametes showed very slight methylation at C-C-G-G. Methylation of additional sites in chlDNA from mt+ gametes but not from mt- gametes was shown by blockage of some EcoRI and BamHI sites that were cleaved in the chlDNA from vegetative cells. chlDNA from 6-hr zygotes was much more methylated than gametic mt+ DNA, as shown by its almost total resistance to cleavage by all four restriction enzymes. These findings support and extend previous evidence that chlDNA of mt+ cells is methylated during gametogenesis and that further methylation occurs after gametic fusion in the young zygotes.